Desenvolvimento de um método alternativo de dessalgação e desidratação de petróleos pesados e extrapesados - Sad, Cristina Maria dos Santos (2019)
In this study, an alternative method of desalting and dehydrating heavy and extra-heavy oils with high water content and dissolved salts was proposed using a prototype of a desalter and a modified rotavaporator. The treatment takes place in two stages of processing: the first one is the desalination by washing with demineralised water and commercial demulsifier, previously tested, for the water-in-oil (W/O) emulsion breaking efficiency and the second stage the desalted oils are dehydrated by rotary evaporation with gradual reduction of pressure in a modified rotary evaporator. Relevant factors to sample homogenization, temperature, time, pressure, recovery test, salt concentration, water and compositional profile by density were investigated with the objective of developing a robust procedure. To determine the best performance parameters of the method was done a model with five oils and for the validation were used 23 heavy and extra heavy oils collected in the production. The modeling results show that desalting and dehydration was successfully performed compared to the conventional method (centrifugation). The best desalting condition was at 60 (5) ºC, with a rotation of 150 rpm for 15 min and after three washing stages, the oils had a mean salt content of 364.5 mg·kg-1 in NaCl , and in the fourth wash the performance was excellent (12.5 mg·kg-1 NaCl). The desalted oils were dehydrated in the rotary evaporator at a temperature of 70 (5) ° C with a pressure reduction gradient of 1000 to 10 mbar in 30 min. The dehydration efficiency was 99.9% with an average water content of 0.69% v/v. The desalting and dehydration time was 75 min, being smaller, compared to the conventional process (around 8 hours). The accuracy of the method was evaluated by the A / O emulsion recovery test with saline water (formation) that showed salt and water removal efficiency of 99.2 and 98.8%, respectively. The results showed that the alternative method presented a better desalting and dehydration performance (35.5 mg·kg-1 NaCl, 0.66% v / v) compared to the conventional method (167.5 mg·kg-1 in NaCl, 1.03% v / v). The compositional profile of the dehydrated oils was evaluated by the measurement of the density indicating that they remained with their compositions unchanged after removal of water and salt.